EVALUASI EMERGENCY RESPONS PLAN PADA KAPAL 42M CREW BOAT BERDASARKAN IMO INTERIM GUIDILINES - Ashari, Mochamad Luqman; Wiediartini, Wiediartini; Dermawan, Denny (Department of Naval Architecture - Diponegoro University, 2013)
Emergency situations that have tendency or potential harm can be happened any time and any where and carry some big damaging impacts to property damages, mental disturbances, injured and died victims. In shipping, emergencies can be happened in both at anchor or while doing loading and unloading activities at the port. The type of equipments used in emergency situations set out in SOLAS Chapter III (Life Saving Appliance) and the guidelines for evacuation analysis on passenger ships refer to the IMO Guidelines Interm MSC/Circ.909. This study aimed to determine the muster station and evacuation time on the ship 42 M crewboats with a capacity of 101passengers. This ship consists of three parts of decks, these are lower part, main deck and bridge deck. The results showed that the placement of muster station is on the bridge deck with required wide 35.35 m2. Evacuation time need by the all passengers to reach the muster station on the bridge deck is 51.59 minutes, and this is in accordance with standard evacuation time (not more than 60 minutes).